Public service for all: How a global ethic prepares public administrators for a transnational century. (2nd January 2018) - Haque, Akhlaque; Gunther-Canada, Wendy
ABSTRACT: In this moment of populist mistrust of globalization and amid attacks on liberal values of democracy, how can we best train the next generation of public administration professionals to serve a citizenry cynical about democratic governance? The article highlights the transnational philosophical underpinnings of global ethic of public service founded on the democratic values of the rule of law and respect for human rights that are vitally important to developing effective, legitimate, and transparent skillsets that promote trust in public administration and democratic governance.